Rapid gene content turnover on the germline-restricted chromosome in songbirds - Schlebusch, Stephen A; Rídl, Jakub; Poignet, Manon; Ruiz-Ruano, Francisco J; Reif, Jiří; Pajer, Petr; Pačes, Jan; Albrecht, Tomáš; Suh, Alexander; Reifová, Radka (Nature communications, 2023)
The germline-restricted chromosome (GRC) of songbirds represents a taxonomically widespread example of programmed DNA elimination. Despite its apparent indispensability, we still know very little about the GRC's genetic composition, function, and evolutionary significance. Here we assemble the GRC in two closely related species, the common and thrush nightingale. In total we identify 192 genes across the two GRCs, with many of them present in multiple copies. Interestingly, the GRC appears to be under little selective pressure, with the genetic content differing dramatically between the two species and many GRC genes appearing to be pseudogenized fragments. Only one gene, cpeb1, has a complete coding region in all examined individuals of the two species and shows no copy number variation. The acquisition of this gene by the GRC corresponds with the earliest estimates of the GRC origin, making it a good candidate for the functional indispensability of the GRC in songbirds.
Keywords: Open Reading Frames; Songbirds; zárodečné buňky; Germ Cells; Animals; biologická evoluce; zpěvní ptáci; otevřené čtecí rámce; chromozomy; Biological Evolution; Chromosomes; zvířata